RNA Binding Motif Protein 15 (RBM15): Structure, Function and Its Research Progress in Tumors - Long X; Hu B; Zhu S; Wu Y; Wang T (International Journal of General Medicine, 2025)
Xiangyu Long,* Bintao Hu,* Shiqing Zhu, Yue Wu, Tao Wang Department of Urology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tao Wang, Department of Urology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China, Email tjhwt@126.comAbstract: N6-methyladenosine (m6A) is the most common modification on mammalian mRNA and has gained considerable attention in recent years as a key regulator of gene expression. RBM15 is an important component of the methyltransferase complex. Although its functions are increasingly being recognized, a comprehensive overview of its critical roles in cancer regulation and potential therapeutic relevance is still lacking. This review aims to summarize recent advances in RBM15 by outlining its physiological functions in normal organisms, detailing its biological roles in tumor regulation and discussing its potential clinical applications. This work highlights its potential as a therapeutic target in oncology.Keywords: RBM15, m6A modification, tumor, therapeutic targets